The pursuit of happiness: A meta-analysis review - Lawal Ibrahim, Zainab; Nadif, Bendaoud (Journal of Interdisciplinary Studies in Education, 2025)
Happiness is being in an emotional state that can reflect a high level of mental and emotional well-being. We examined and explored the factors influencing happiness such as culture, socio-economic status (SES) and religious coping. It also identified the foremost and major factors influencing happiness. In this study the cultural indicators are (early marriage, gender roles and inequality), socio-economic status (parent’s income, education, occupation and social status), and religious coping (passive, active, benevolent and practice). A systematic literature review on the relationship between culture, socio-economic status and religious coping with happiness among female students (Muslim and Christian) was conducted. A total number of 52 articles from various disciplines have been explored. The factors found were divided into those that belong to happiness predicted by culture, socio-economic status and religious coping; factors related to culture, socio-economic status and religious coping related to happiness; mediating effect of religious coping on the relationship of happiness related to culture, socio-economic status and religious coping; and happiness model based on culture, socio-economic status and religious coping factors. Culture, socio-economic status and religious coping were found to predict and be related to happiness.